2012
DOI: 10.3390/molecules18010322
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Underlying Anti-Inflammatory and Anti-Allergic Activities of Phytochemicals: An Update

Abstract: The resort worldwide to edible medicinal plants for medical care has increased significantly during the last few years. Currently, there is a renewed interest in the search for new phytochemicals that could be developed as useful anti-inflammatory and anti-allergic agents to reduce the risk of many diseases. The activation of nuclear transcription factor-kappa B (NF-κB) has now been linked to a variety of inflammatory diseases, while data from numerous studies underline the importance of phytochemicals in inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(137 citation statements)
references
References 207 publications
3
126
0
8
Order By: Relevance
“…47 Recent research also confirmed that quercetin as one of active compound from M. fragrans can inhibit various cytokines including TNF-α, IL-6, and IL-1β. 15,16,31,48,49 NO plays a significant role in host immune defense, vascular regulation, neurotransmission, and other system in normal condition. Overproduction of inducible NO Synthase (iNOS) is especially related to various human diseases including inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…47 Recent research also confirmed that quercetin as one of active compound from M. fragrans can inhibit various cytokines including TNF-α, IL-6, and IL-1β. 15,16,31,48,49 NO plays a significant role in host immune defense, vascular regulation, neurotransmission, and other system in normal condition. Overproduction of inducible NO Synthase (iNOS) is especially related to various human diseases including inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Morusin which has been isolated from the root bark of Morus alba L. (Moraceae), known and read as SangBekPi in Republic of Korea, possesses various biological activities including antimicrobial, scavenging against superoxide anion radical and anti-inflammatory activities (1)(2)(3). Previous studies have indicated that morusin suppresses cancer cell growth, and induces cell death in cervical cancer, hepatoma, glioma and prostate cancer (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…This yielded 1.55 g (65.9 %) of white crystal with a melting point of 69.0-69.5°C. Analysis with 1 3,3',4',7-tetrapivaloylquercetin (3) was analogously synthesized according to the procedure reported by Mattarei, et al [10]. Pivaloyl chloride (12.06 ml, 0.1 mol) was added dropwise and under continuous stirring to a mixture of quercetin (1.55 g, 5 mmol) and anhydrous pyridine (4.25 ml, 50 mmol) that was previously cooled in a dry ice bath.…”
Section: Methodsmentioning
confidence: 99%
“…When intraperitoneally administered, quercetin decreases the production of edema in the acute phase after carrageenan injection, but has no significant action on the chronic phase [3,4]. Quercetin has also been reported to promote antioxidant enzyme activity, prevent free radical attacks as well as enhance endogenous antioxidant molecules [1]. In addition, quercetin possesses gastric protective and gastric ulcer healing-promoting action [5], so quercetin was chosen as lead compound for the development of anti-inflammatory agents with low-risk of gastrointestinal toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation